Microcredit and development: a multi-level examination of women's participation in microfinance institutions. Issue 3 (3rd April 2017) - Bezboruah, Karabi; Pillai, Vijay
ABSTRACT: International organisations promote microcredit as a tool for socio-economic development by targeting women's entrepreneurial capabilities. There is limited research, however, on the variation in women's participation in microcredit in developing nations. To understand this variation, this article examines the relationship between a country's gender equality levels and women's microcredit participation. The results indicate that participation is higher when loans are small; however, with increases in gender equality levels, participation decreases. Women in countries with higher gender inequality are limited to very small loans and questionable economic improvements, suggesting that microcredit needs to be utilised contextually to be an effective developmental tool.